A testimony about home dialysis in Tougué (Guinea) using the NxStage® portable haemodialysis system - Alhassane Diallo (RDPLF, 2022)
Several testimonials have already appeared in the Bulletin de la Dialyse à Domicile or the website of the French-language Peritoneal Dialysis Registry detailing patient experiences remarkable for their empowerment at home (1), or for the achievement of sports and human challenges such as that of Fabrice HURE (2) or Jean Louis CLEMENDOT (3). The testimony we report is the travel story of Mr Alhassane DIALLO, a dialysis patient who wanted to join his family in Guinea at a great distance from any dialysis clinic, a journey that home dialysis allowed, but not without hardships. We hope that this experience can help other patients with independent travel plans. The success of this project was due to the unwavering determination of Mr DIALLO but also to a collective organization that requested the administrative, logistical and pharmacy services of the AUB Santé Foundation and close cooperation between the French and Guinean medical teams. This experience shows us how important travel limitations are in the experience of dialysis patients, and particularly in that of expatriate patients. In addition, it highlights the significant inequalities in access to care in the world: Guinea has only one dialysis centre, in Conakry. Eric LARUELLE, MD, Nephrologist, AUB Santé Foundation* Picault, Christelle. 2019. « Dialyse Longue Nocturne à Domicile à Bas débit De Dialysat. ». Bulletin De La Dialyse à Domicile 2 (1), 33-36. https://doi.org/10.25796/bdd.v2i1.19143. 2/ Fabrice Huré. La montagne dans le sang. Un témoignage humain d'un patient dialysé de nuit pour les autres patients. Bulletin Dialyse Domicile N°1.Vol 2. Avril 2019 DOI : https://doi.org/10.25796/bdd.v2i1.19153 3/ Témoignages : la traversée de l'Atlantique en solitaire en dialyse péritonéale. https://www.rdplf.org/information-patients/temoignages-patients.html?id=337